Queen's Park Hotel, Port-of-Spain - (:unkn) unknown (My University, 2010)
The Queen's Park Hotel, located in Port of Spain on the Southern side of the Queen's Park Savannah, was first opened in January 1895.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Historic hotels--Trinidad and Tobago; Hotels--Trinidad and Tobago; [1920]; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Fences--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)